Criterion-related validity of 2-Dimensional measures of hip, knee and ankle kinematics during bilateral drop-jump landings - Iñaki Ruiz-Pérez; José LL Elvira; Gregory D Myer; Mark De Ste Croix; Francisco Ayala (Asociación Española de Ciencias del Deporte, 2021)
Three-dimensional (3D) motion capture systems have been used to identify athletes in high risk of injury, but due to their cost, lack of portability and qualified technicians, an alternative is needed, such as two-dimensional (2D) systems. The purpose of this study was to examine the criterion-related validity of three measures of frontal plane knee alignment (Frontal plane projection angle [FPPA], knee-to-ankle separation ratio [KASR] and knee medial displacement [KMD]) and two sagittal plane measures (hip and knee flexion ranges of motion [ROMs]), recorded simultaneously using a 2D video analysis procedure and a 3D motion analysis system. Twenty-nine male futsal players had frontal and sagittal plane kinematics assessed while performing bilateral drop vertical jumps (DVJ). The criterion-related validity of the frontal and sagittal plane kinematic measures obtained using the 2D video analysis procedure and 3D motion system was determined through the estimation equation, typical error of the estimate (TEEST) and validity correlation (r). Kappa correlations were also calculated to determine the agreement between the 2D and 3D kinematic approaches. The results showed poor validity for the FPPA measure (standardized TEEST = 1.34 [large], r = 0.60) and moderate validity for KASR (standardized TEEST = 0.88 [moderate], r = 0.77), KMD (standardized TEEST = 0.53 [small], r = 0.88), hip flexion ROM (standardized TEEST = 0.62 [moderate], r = 0.85) and knee flexion ROM (standardized TEEST = 0.56 [small], r = 0.87) measures. However, only the KMD and knee flexion ROM measures showed high levels of agreement (kappa > 0.7). Therefore, the KMD and knee flexion ROM measures calculated during a bilateral DVJ and using a 2D video analysis procedure might be considered as valid and feasible alternatives to their respective 3D criterion to quantify knee kinematics and to detect futsal players who demonstrated aberrant movement patterns in the frontal and sagittal planes, respectively.